Dark Pigments in Entomopathogenic Fungal Microsclerotia: Preliminary Evidence of a 1,8-Dihydroxynaphthalene-melanin-like Compound in Metarhizium robertsii - Espin Sanchez, Daysi de Lourdes (2023)
Metarhizium robertsii microsclerotia are fungal aggregates composed of compacted, pigmented hyphae. As they are highly tolerant to desiccation and produce infective conidia, they are promising candidates to be formulated as bioinsecticides. Despite this potential, the nature of the pigments within these structures remains unclear. In this study, routine culture media used for the differentiation of M. robertsii microsclerotia were supplemented with four melanin inhibitors, and the resulting propagules were characterized. Inhibitors of the 1,8-dihydroxynaphthalene (DHN)-melanin biosynthetic pathway such as tricyclazole and guaiacol induced significant phenotypic and molecular modifications in the obtained M. robertsii propagules, which exhibited a more spherical shape, reduced size, and increased susceptibility to desiccation, heat, and oxidative stress than microsclerotia obtained without inhibitors. Additionally, genes encoding for a polyketide synthase (Mrpks2) and a putative 1,3,6,8-tetrahydroxynaphthalene reductase (Mrthnr), potentially involved in the DHN-melanin biosynthetic pathway, were upregulated in fungi grown in the inhibitor-added media. In conclusion, M. robertsii microsclerotia contain melanins of type DHN that might play a role in both microsclerotia differentiation and environmental stress tolerance.